Grade Migration of Prostate Cancer in the United States During the Last Decade. (28th March 2022) - Borregales, Leonardo D; DeMeo, Gina; Gu, Xiangmei; Cheng, Emily; Dudley, Vanessa; Schaeffer, Edward M; Nagar, Himanshu; Carlsson, Sigrid; Vickers, Andrew; Hu, Jim C
Abstract: Background: Prostate cancer (PC) screening guidelines have changed over the last decade to reduce overdiagnosis and overtreatment of low-grade disease. We sought to examine and attempt to explain how changes in screening strategies have impacted temporal trends in Gleason grade group (GG) PC at diagnosis and radical prostatectomy pathology. Methods: Using the Surveillance, Epidemiology, and End Results Registry database, we identified 438 432 men with newly diagnosed PC during 2010-2018. Temporal trends in incidence of GG at biopsy, radical prostatectomy pathology, prostate-specific antigen (PSA) level, and metastasis at diagnosis were examined. The National Health Interview Survey database was examined to evaluate trends in PSA-screening rates, and a literature review evaluating magnetic resonance imaging and biomarkers utilization during this period was performed. Results: Between 2010 and 2018, the incidence of low-grade PC (GG1) decreased from 52 to 26 cases per 100 000 ( P  < .001). The incidence of GG1 as a proportion of all PC decreased from 47% to 32%, and the proportion of GG1 at radical prostatectomy pathology decreased from 32% to 10% ( P  < .001). However, metastases at diagnosis increased from 3.0% to 5.2% ( P  < .001). During 2010-2013, PSA screening rates in men aged 50-74 years declined from 39 to 32 per 100 men and remained stable. Utilization rates of magnetic resonance imaging and biomarkers modestly increased from 7.2% in 2012 to 17% in 2019 and 1.3% in 2012 to 13% in 2019, respectively. Conclusions: We found a significant decrease in the diagnosis and treatment of GG1 PC between 2010 and 2018. Changes in PSA screening practices appear as the primary contributor. Public health efforts should be directed toward addressing the increase in the diagnoses of metastatic PC.